2012
DOI: 10.4049/jimmunol.1102079
|View full text |Cite
|
Sign up to set email alerts
|

UXT-V1 Facilitates the Formation of MAVS Antiviral Signalosome on Mitochondria

Abstract: Virus infection induces the MAVS–TNFR-associated factor (TRAF) 3 signaling axis on mitochondria. It remains to elucidate the corresponding regulatory processes. In this study, we identify UXT-V1 as a novel TRAF3-binding protein. UXT-V1 is critical for the virus-induced activation of NF-κB and IFN regulatory factor 3. Reduction of UXT-V1 impairs the induction of IFN-β and attenuates the host antiviral responses. The N-terminal TRAF-binding motif of UXT-V1 binds to the C-terminal TRAF domain of TRAF3, thus facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 42 publications
(47 reference statements)
2
27
0
3
Order By: Relevance
“…The observation that a GnT tyrosine is critical for TBK1 regulation suggests a potential role for tyrosine regulation of IRF3 activation, although Y627 is reportedly not phosphorylated (48,49). However, RAUL, OTUD7B, Fox01, and E3 ligase regulators may be impacted by GnTs and alter the ubiquitination of TBK1, NEMO, TRAF3, IRF3/7, or NF-B required for IFN-␤ induction (34,40,44,45,54,58,61,62,65,66). These factors provide an array of potential GnT targets IFN regulation; however, the mechanism by which GnTs inhibit TBK1-directed IRF3 and NF-B activation remains to be revealed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that a GnT tyrosine is critical for TBK1 regulation suggests a potential role for tyrosine regulation of IRF3 activation, although Y627 is reportedly not phosphorylated (48,49). However, RAUL, OTUD7B, Fox01, and E3 ligase regulators may be impacted by GnTs and alter the ubiquitination of TBK1, NEMO, TRAF3, IRF3/7, or NF-B required for IFN-␤ induction (34,40,44,45,54,58,61,62,65,66). These factors provide an array of potential GnT targets IFN regulation; however, the mechanism by which GnTs inhibit TBK1-directed IRF3 and NF-B activation remains to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…required for binding to MAVS and UXT-V1 as well as for the downstream recruitment of TBK1 to MAVS complexes (Fig. 3A) (36,45,61). To investigate GnT regulatory interactions, we analyzed TRAF3 domains required for binding to the GnT using C-terminal truncations of TRAF3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both UXTV1 and UXTV2 are ubiquitous in mouse and human cell lines but UXTV1 is less abundantly expressed [Huang et al, ]. Most of the studies to date have focused on the functions of UXTV2, while UXTV1 has been implicated in TNF‐induced apoptosis [Huang et al, ]. In this study, UXTV2 was specifically identified as a novel LOX‐PP associating protein, and is subsequently referred to as UXT.…”
mentioning
confidence: 94%
“…Besides protein methylation, multiple transcription co-regulators have been found to be involved in the activation of NF-κB target genes. For example, the ubiquitously expressed prefoldin-like chaperone UXT (also known as STAP1 and ART-27), a small chaperone-like protein, has been reported to interact with the p65 subunit of NF-κB (also known as RELA) and functions as a transcription co-activator, as well as a cytoplasmic regulator for anti-viral pathway (Huang et al, 2011(Huang et al, , 2012Sun et al, 2007). However, how UXT contributes to the activation of NF-κB target genes is still not clear.…”
Section: Introductionmentioning
confidence: 99%